2009
DOI: 10.1111/j.1439-0531.2009.01485.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Subclinical Endometritis in the Mare: Both Threats to Fertility

Abstract: Endometritis, a major cause of mare infertility arising from failure to remove bacteria, spermatozoa and inflammatory exudate post-breeding, is often undiagnosed. Defects in genital anatomy, myometrial contractions, lymphatic drainage, mucociliary clearance, cervical function, plus vascular degeneration and inflamm-ageing underlie susceptibility to endometritis. Diagnosis is made through detecting uterine fluid, vaginitis, vaginal discharge, short inter-oestrous intervals, inflammatory uterine cytology and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
260
0
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(284 citation statements)
references
References 98 publications
(219 reference statements)
8
260
0
16
Order By: Relevance
“…Clinical findings are substantiated by inflammatory uterine cytology (Knudsen 1964, Wingfield Digby and Ricketts 1982, Riddle et al 2007, Leblanc and Causey 2009 and positive uterine culture (Dimmock and Edwards 1923, Brook 1984, Riddle et al 2007). Collecting samples from the uterus is a routine practice in the assessment of uterine health.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical findings are substantiated by inflammatory uterine cytology (Knudsen 1964, Wingfield Digby and Ricketts 1982, Riddle et al 2007, Leblanc and Causey 2009 and positive uterine culture (Dimmock and Edwards 1923, Brook 1984, Riddle et al 2007). Collecting samples from the uterus is a routine practice in the assessment of uterine health.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian activity disorders that may cause infertility should be evaluated, and pathological changes in the reproductive organs, such as intrauterine fluid accumulation, can be detected during an ultrasonographic examination (2). Endometritis, which is one of the major causes of infertility in mares, is caused by inadequate bacterial inhibition, spermatozoa removal from the uterus, and inflammatory exudates after breeding (3). Although clinical endometritis is diagnosed easily, uterine culture, cytology, and endometrial biopsy are important tools along with ultrasonography examination that enable diagnosis of subclinical cases of endometritis (3).…”
Section: Introductionmentioning
confidence: 99%
“…Endometritis, which is one of the major causes of infertility in mares, is caused by inadequate bacterial inhibition, spermatozoa removal from the uterus, and inflammatory exudates after breeding (3). Although clinical endometritis is diagnosed easily, uterine culture, cytology, and endometrial biopsy are important tools along with ultrasonography examination that enable diagnosis of subclinical cases of endometritis (3). Previous studies have suggested that only uterine cytology or bacteriology (4) or a combination of both (4,5) can be used to determine uterus inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to remove bacteria, spermatozoa and inflammatory exudate post-breeding may lead to inflammation of endometrium. Moreover, the factors which underlie susceptibility to endometritis are: defects in genital anatomy, impaired myometrial contractions, impaired immune defense, overproduction of mucus and inadequate lymphatic drainage, abnormal mucociliary clearance and cervical function (Watson, 2000;LeBlanc & Causey, 2009;LeBlanc, 2010). Uterine inflammation has been proposed as a mechanism for impaired myometrial contractility and accumulation of inflammatory products in the uterine lumen (Troedsson et al, 1993;Troedsson, 1999).…”
Section: Introductionmentioning
confidence: 99%